Correction: Tracking the incidence and risk factors for SARS-CoV-2 infection using historical maternal booking serum samples - Mullins,E; McCabe,R; Bird,SM; Randell,P; Pond,MJ; Regan,L; Parker,E; McClure,M; Donnelly,CA (PLoS One, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0273966.].